Different dimensions of knee joint and their gender variations among adult Bangladeshi population (Bangladesh Medical Journal Khulna, 2025)
Background: Human knee shows significant variation in different radiographic dimensions. Different knee joint dimensions can be studied by visual observation, anthropometric measures and radiographic measures. Among these methods, radiographic measurements were regarded as most important for assessing skeletal alignment of knee joint in a static weight bearing position. Objective: The present study was aimed for finding out the differences in dimensions of knee joint between adult Bangladeshi male and female. Methods: A cross-sectional analytical type of study was carried out in the Department of Anatomy, Dhaka Medical College, Dhaka from July, 2018 to June, 2019. The study population was adult Bangladeshi male and female attending the Radiology and Imaging department of Dhaka Medical College and Hospital (DMCH) for the X-ray advised by their physicians. Digital radiographs of antero-posterior and lateral view of knee joint were taken. Results: The study was performed on 80 Bangladeshi population where 40 was male and 40 was female. In male, the mean interepicondylar distance (IED) was 71.87±3.73 mm, intermetaphyseal diameter (IMD) was 69.32±3.61 mm, femoral width (FW) was 66.72±3.61 mm and tibial width (TW) was 69.11±2.66 mm. In female, the mean interepicondylar distance (IED) was 63.48 ±3.67 mm, intermetaphyseal diameter (IMD) was 61.80 ±4.49 mm, femoral width (FW) was 59.21 ±3.86 mm and tibial width (TW) was 61.85 ±3.89 mm. The mean (±SD) of all distances were found to be more in male than in female. Conclusion: In the present study, interepicondylar distance (P